Thermal optimization of buoyancy driven radiative engine-oil based viscous hybrid nanofluid flow observing the micro-rotations in an inclined permeable enclosure - Kamil Abbas; Wang Xinhua; Ghulam Rasool; Tao Sun; Izzat Razzaq (Case Studies in Thermal Engineering, 2024)
Thermal enhancement of engine oil plays an important role in a variety of industrial applications including heat exchangers, automotive cooling systems, renewable energy systems, biomedical devices, and advanced manufacturing processes. Considering the high demand in industry, present investigation explores thermal optimization of engine oil contained in a porous inclined cavity involving dispersion of hybrid nanoparticles along with inclusion of micropolar fluid flow phenomena. Numerical analysis is performed on the micropolar nanofluid containing iron oxide and molybdenum disulfide while considering the effect of thermal radiation, buoyancy force, viscous dissipation, magnetic field’s strength, porosity, and vortex viscosity. Numerical solutions of the dimensionless governing equations are provided through utilization of FVM. The coupling of velocity and pressure terms was achieved through implementation of SIMPLE algorithm. The results are illustrated through streamlines, contours, velocity, temperature profiles and heat flux. The outcomes revealed that an augment in Hartmann number and thermal radiation parameter results in higher heat flux rate. The incrementation in Hartmann number disrupted the flow resulting a reduction in the size of major vortices and similar trend is noted in case of temperature profile for the said parameters. The outcomes complement the continuing efforts to improve the thermal management of various applications and offer insightful information for optimizing engine oil compositions.